Identifying Zoonotic Parasites in Domiciled and Non‐Domiciled Dogs (Canis lupus familiaris) Within an Urban Zone of the Eastern State of Mexico - José Salcedo‐Jiménez; Yazmín Alcala‐Canto; Julio Segura‐Tinoco; Ernestina Valadez‐Moctezuma; Juan José Pérez‐Rivero (Veterinary Medicine and Science)
ABSTRACT Background There are over 42 million dogs in Mexico, with a significant population living on the streets, especially in the State of Mexico. These dogs can act as carriers of zoonotic pathogens, placing children and individuals with chronic diseases or immunodeficiencies at risk. Objectives To evaluate the prevalence of zoonotic parasites in feral and domestic dogs in the urban area of the eastern State of Mexico and assess their potential impact on public health. Methods The study was conducted from July 2022 to March 2023 in the urban area located in the eastern region of the State of Mexico. A total of 134 samples of dog faces were collected through convenience sampling, from both domiciled and non‐domiciled dogs. Results Fifty‐one dogs were identified with Ancylostomatidae family (38.1%, 95% CI: 27.0%–52.1%), 10 with Toxocara spp. (7.5%, 95% CI: 3.6%–13.3%), 7 with Dipylidium caninum (5.5%, 95% CI: 2.1%–10.5%), 8 with Cystoisospora spp. (6.0%, 95% CI: 2.6%–11.4%), 6 with Giardia spp. (4.5%, 95% CI: 1.7‐9.5%) and 2 positive cases for Hymenolepis spp. (1.5%, 95% CI: 0.2%–5.3%) were identified. Conclusions This study highlights a public health concern related to non‐domiciled dogs, which can serve as carriers of zoonotic parasites. Interactions among non‐domiciled dogs, domiciled dogs and humans heighten the risk of transmission. Implementing prevention, control and awareness strategies is crucial to reduce the spread of these parasites.